Lipidomic and transcriptomic profiles provide new insights into the triacylglycerol and glucose handling capacities of the Arctic fox - Zhu, Yuhang; Yuan, Yuan; Si, Huazhe; Li, Songze; Zhao, Fei; Mu, Ruina; Lin, Zihan; Wang, Xiaoxu; Qiu, Qiang; Xu, Chao; Ji, Lele; Li, Zhipeng (Frontiers in Veterinary Science, 2024)
The Arctic fox (Vulpes lagopus) is a species indigenous to the Arctic and has developed unique lipid metabolism, but the mechanisms remain unclear. Here, the significantly increased body weight of Arctic foxes was consistent with the significantly increased serum very-low-density lipoprotein (VLDL), and the 40% crude fat diet further increased the Arctic fox body weight. The enhanced body weight gain stems primarily from increased subcutaneous adipose tissue accumulation. The adipose triacylglycerol and phosphatidylethanolamine were significantly greater in Arctic foxes. The adipose fatty-acid synthase content was significantly lower in Arctic foxes, highlighting the main role of exogenous fatty-acids in fat accumulation. Considering the same diet, liver-derived fat dominates adipose expansion in Arctic foxes. Liver transcriptome analysis revealed greater fat and VLDL synthesis in Arctic foxes, consistent with the greater VLDL. Glucose homeostasis wasn't impacted in Arctic foxes. And the free fatty-acids in adipose, which promote insulin resistance, also didn't differ between groups. However, the hepatic glycogen was greater in Arctic foxes and transcriptome analysis revealed upregulated glycogen synthesis, improving glucose homeostasis. These results suggest that the superior fat accumulation capacity and distinct characteristics of hepatic and adipose lipid and glucose metabolism facilitate glucose homeostasis and massive fat accumulation in Arctic foxes.